The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s11412-006-9002-0
|View full text |Cite
|
Sign up to set email alerts
|

Electronic [re]constitution of groups: Group dynamics from face-to-face to an online setting

Abstract: The authors work as online tutors for a BSc (Hons) physiotherapy programme at Coventry University in the United Kingdom. This paper represents a stage in our developing understanding, over a 3 year period, of the impact of group dynamics on online interaction among physiotherapy students engaged in sharing with their peers their first experiences of clinical practice. The literature exploring online interaction tends to situate meaning either in theories borrowed from conventional face-to-face interaction or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, it takes time for team partners to share the missions and understand the goals, and it is expected to see varying levels of resistance from team members. Collaborative skills such as collegial enquiry and reflection are needed to resolve conflicts (Clouder et al, 2006;Pedder & MacBeath, 2008), and engaging in collaborative learning seems to be a promising way to develop these collaborative skills (Chai & Tan, 2009;Laurillard, 2009). Team teaching may be most effective when it is "team learning" (Tajino & Tajino, 2000), in which team teachers are encouraged to engage jointly in information exchange, consultation, and transfer of responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, it takes time for team partners to share the missions and understand the goals, and it is expected to see varying levels of resistance from team members. Collaborative skills such as collegial enquiry and reflection are needed to resolve conflicts (Clouder et al, 2006;Pedder & MacBeath, 2008), and engaging in collaborative learning seems to be a promising way to develop these collaborative skills (Chai & Tan, 2009;Laurillard, 2009). Team teaching may be most effective when it is "team learning" (Tajino & Tajino, 2000), in which team teachers are encouraged to engage jointly in information exchange, consultation, and transfer of responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…This model of learning usually consists of video/audio conferences and instant messaging through cameras and microphones. The use of synchronous learning approaches enhances student engagement, supports group identity, and enables timely feedback from instructors (Brown et al, 2016;Clouder et al, 2006;Falloon, 2011). In asynchronous learning, instead of meeting virtually in real-time, learners go through the learning process at their convenience of time and location (Moore, 2016).…”
Section: Literature Review 21 Online Learningmentioning
confidence: 99%
“…For example, Professor Lynn Clouder et al found that when group interactions shifted from a face-to-face setting to an asynchronous online setting, the role of the online facilitator "cannot be underestimated" and that the professor serves "as a central feature of the model and a link from one context to the other." 254 time-management skills. 259 One might expect that, on the whole, law students and other graduate students are more likely than undergraduate students to be self-disciplined.…”
Section: Components Of a Quality Online Coursementioning
confidence: 99%